2021
DOI: 10.3390/en14217206
|View full text |Cite
|
Sign up to set email alerts
|

Battery State-of-Health Estimation Using Machine Learning and Preprocessing with Relative State-of-Charge

Abstract: Because lithium-ion batteries are widely used for various purposes, it is important to estimate their state of health (SOH) to ensure their efficiency and safety. Despite the usefulness of model-based methods for SOH estimation, the difficulties of battery modeling have resulted in a greater emphasis on machine learning for SOH estimation. Furthermore, data preprocessing has received much attention because it is an important step in determining the efficiency of machine learning methods. In this paper, we prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Examples of data-driven methods include a support vector machine (SVM) [25][26][27][28][29], random forest (RF) [30,31], artificial neural networks (ANNs) [32][33][34][35][36][37], recurrent-neural networks (RNNs) [38], and variants such as long short-term memory (LSTM) [39][40][41][42][43][44] and a nonlinear autoregressive network with exogenous inputs (NARX) [45][46][47]. ANNs learn from historical data to predict future behavior, i.e., the learning procedure exploits a dataset representative of the battery behaviour to make predictions.…”
Section: Related Workmentioning
confidence: 99%
“…Examples of data-driven methods include a support vector machine (SVM) [25][26][27][28][29], random forest (RF) [30,31], artificial neural networks (ANNs) [32][33][34][35][36][37], recurrent-neural networks (RNNs) [38], and variants such as long short-term memory (LSTM) [39][40][41][42][43][44] and a nonlinear autoregressive network with exogenous inputs (NARX) [45][46][47]. ANNs learn from historical data to predict future behavior, i.e., the learning procedure exploits a dataset representative of the battery behaviour to make predictions.…”
Section: Related Workmentioning
confidence: 99%
“…A CNN is combined with a gated recurrent neural network in [12] and two CNNs are used with random forest in [13], with both combinations showing improved SOH estimation. Finally, a different method of sampling data, at fixed SOC steps rather than fixed time steps, was shown to be beneficial for battery SOH estimation with a CNN, FNN, or LSTM [14].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [24] have trained a CNN model to predict battery capacity based on the observed impedance and SoC variables collected during the experiment. After all that, it has been demonstrated that using a different sampling strategy, such as defined SoC phases rather than defined time steps, is useful for battery SoH estimation when using FNN, CNN, or LSTM [25]. SoC estimate using a Nonlinear Autoregressive Exogenous neural network (NARX) is of specific interest to Zhang [26], who plans to contrast the anticipated outcome with that obtained using EKF.…”
Section: Introductionmentioning
confidence: 99%